Advances in the study of risk factors and screening strategies for chronic obstructive pulmonary disease - WANG Na; CHEN Yue (Shanghai yufang yixue)
Chronic obstructive pulmonary disease (COPD) is a major public health issue in China, imposing a substantial disease burden to the patient’s family and the whole society. This article reviews COPD risk factors from both individual and environmental dimensions, discusses advances in early screening and diagnostic strategies for COPD, aiming to inform prevention and control measures to reduce the burden of COPD.